Effects of Diet and Physical Activity on Coronary Heart Disease Risk Among Badminton Players - Priyono, Eko; Ma'mun, Sukrul (SAFE-Network, 2024)
Coronary heart disease is caused by the narrowing or blockage of coronary arteries due to the buildup of fat and cholesterol, which hinders blood flow to the heart. This study aims to determine the relationship between dietary patterns and physical activity with coronary heart disease in the badminton player community in Indonesia. This research uses a cross-sectional design. The sample was taken using accidental sampling, involving 100 badminton players from various clubs in Indonesia. Data were collected using a questionnaire on June 24-27, 2024, and analyzed with SPSS using the chi-square test. The results showed that 100% of respondents did not have coronary heart disease, 64% often consumed carbohydrates, 71% often consumed protein, 71% rarely consumed fat, 56% rarely consumed fiber, 73% rarely consumed cholesterol, and 79% had heavy physical activity. The chi-square test showed a significant relationship between heavy physical activity and a family history of coronary heart disease (p-value = 0.036) and a nearly significant relationship between fat consumption and a family history of coronary heart disease (p-value = 0.066). The odds ratio showed a significant value (p-value = 0.019). These results indicate that there may be a relationship between the variables tested, although the Pearson Chi-Square did not reach conventional significance, requiring further research for confirmation.